(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: Nocturnal enuresis is an innocent but distressing disorder occurring in many children which may lead to poor self-esteem. Objectives: To evaluate the response of a group of children with nocturnal enuresis to intranasal Desmopressin or oral Oxybutynin HCl, and compare the response to both drugs. Subjects & Methods: This prospective study was done over 4 weeks period. Patients were 25 children aged 6-13 years with severe nocturnal enuresis; they were divided into two groups. First group = 17 children received intranasal Desmopressin 20 μg; if no response, increased to 40 μg. Second group = 8 children received Oxybutynin HCl orally one tablet (5 mg), if no response; increased to 2 tablets. Response was regarded as a decrease in number of wet nights per week, and divided into 3 categories: full responders with 0-1 wet night /week, intermediate with 2-3 wet nights/ week and non-responders with > 3 wet nights / week. Results: The response rate to Desmopressin was 82.4%; 53% of them were full responders, while the response rate to Oxybutynin HCl was 50%; 25% of them were full responders. The mean number of wet nights/week for the total 4 weeks therapy for the Desmopressin group was (2.1±1.9) and for the Oxybutynin HCl group was (3.8±2.8). There was a highly significant difference before and after therapy in the Desmopressin group (P<0.001). None of the children developed side effect to Desmopressin, one child had side effect to Oxybutynin HCl. Conclusion: For short-term therapy over 4 weeks, Desmopressin was safe and highly effective in the treatment of nocturnal enuresis. Oxybutynin HCl was less effective with some side effect. Further studies for longer periods are needed. Key words: Nocturnal enuresis, Desmopressin, Oxybutynin HCl Iraqi J Med Sci, 2004; Vol. 3 (1): 93-97